2017
DOI: 10.1186/s41100-017-0095-x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of nutritional intervention by dietitians for hyperphosphatemia in maintained hemodialysis patients

Abstract: Hyperphosphatemia is a risk factor for cardiovascular disease and mortality in individuals with end-stage kidney disease (ESKD). Thus, it represents a potential target for interventions to improve clinical outcomes in ESKD. Phosphorus reduction therapy for maintained hemodialysis (MHD) patients encompasses phosphate binder medication, adequate dialysis, and also dietary phosphorus control. The main strategy in achieving dietary phosphorus reduction involves intensive education by a dietitian. The purposes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Several experimental studies have demonstrated the potent cytotoxic and procalcific Ca-phosphate crystals in the absence of fetuin-A [156,157] . A decrease in systemic fetuin-A increases systemic calciprotein particles and procalcification of calciprotein particles, thus promoting vascular calcification [158][159][160][161][162] .…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have demonstrated the potent cytotoxic and procalcific Ca-phosphate crystals in the absence of fetuin-A [156,157] . A decrease in systemic fetuin-A increases systemic calciprotein particles and procalcification of calciprotein particles, thus promoting vascular calcification [158][159][160][161][162] .…”
Section: Discussionmentioning
confidence: 99%
“…This program was prepared clearly and simply for participants because it was assumed that some participants were probably illiterate. The content was developed based on the latest scientific sources [ 1 , 4 , 8 , 17 – 19 ] and then its content validity was confirmed by two nephrologists and a nutritionist. The program was implemented in four 15–30 min sessions held for HPs with hyperphosphatemia and their FCGs during hemodialysis.…”
Section: Methodsmentioning
confidence: 99%
“…Dietitians can help reduce the stress of adhering to a restricted diet by providing practical, achievable recommendations, rather than compelling patients to give up their favorite foods. 25 For example, patients could be advised to eat fresh, nonprocessed egg whites instead of cutting out eggs entirely. 25 Visual aids that allow patients to quickly check which foods are safe to eat, without needing to memorize the phosphate load for each item, help alleviate the stress and anxiety of adhering to a restricted diet.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…25 For example, patients could be advised to eat fresh, nonprocessed egg whites instead of cutting out eggs entirely. 25 Visual aids that allow patients to quickly check which foods are safe to eat, without needing to memorize the phosphate load for each item, help alleviate the stress and anxiety of adhering to a restricted diet.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%